Nurses' performance to the elderly with delirium in intensive care: experience report (Research, Society and Development, 2020)
Objective: to describe an experience of nurses in the treatment of elderly patients with delirium who underwent highly complex surgery hospitalized in Intensive Care Units (ITU). Method: This is an experience report by a nurse, a specialist in cardiology with experience in high complexity postoperative periods and a nursing supervisor in a private hospital in the State of Rio de Janeiro, about the nursing performance in patient care elderly with delirium in an intensive care unit of a private hospital in Rio de Janeiro. Results: the report describes a trajectory of nurses in the care of elderly patients in intensive care with delirium, relating their difficulties and challenges in the case of prevention, identification and treatment of these patients. Subsequently, it demonstrates the performance of the nursing coordinator of the intensive care units and his posture in face of the difficulties faced by patients with delirium. Finally, it describes the role of the administrative nursing supervisor in the training laboratory for nursing professionals through lectures. Conclusion: Thus, it appears that investment in updating and training of nursing teams is crucial for there to be specific assistance in damages in the care of the elderly with delirium in the intensive care unit.